PERBANDINGAN KINERJA KEUANGAN DAN ANALISIS KEBUTUHAN MODAL KERJA PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA MAYANG KOTA JAMBI DAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA SAKTI KABUPATEN KERINCI (PERIODE TAHUN 2013-2017) - Wahyu, Wawan Devis; Rahayu, Sri; Machpudin, Asep (LPPM Universitas Adiwangsa Jambi, 2019)
The purpose of this study is to determine and analyze the comparison of financial performance of PDAM Tirta Mayang Kota Jambi and PDAM Tirta Sakti Kabupaten Kerinci. Another purpose is to know the adequacy of working capital and analyze the amount of working capital needs in PDAM Tirta Mayang Kota Jambi and PDAM Tirta Sakti Kabupaten Kerinci 2013-2017. The method used is Comparative. The results of this study indicate: (1) The calculation results of Minister of Internal Affairs number 47 in 1999 show no significant difference to the financial performance of the two companies. (2) Based on the analysis of the table shows that the analysis of working capital requirement in PDAM Tirta Mayang Kota Jambi and Tirta Sakti PDAM Kabupaten Kerinci fluctuated during the last 5 years. In 2015 the largest working capital needs analysis of PDAM Kota Jambi with the number Rp 36.725.261.051.55, while in 2017 the largest working capital requirement analysis PDAM Kabupaten Kerinci with the number Rp13.589.692.686,57. In 2013 the working capital requirement analysis of PDAM Kota Jambi is the smallest with the number Rp 22.484.602.508,19, while in 2014 the working capital requirement analysis of PDAM of Kerinci Regency is the smallest with the number Rp5.573.143.108,43. With average working capital requirement for PDAM Kota jambi is Rp23.661.204.073,25 and Rp7.568.176.762,16 for PDAM Kabupaten Kerinci.